Analysis of Greenhouse Gas Emission Load and Emission Reduction from Switching to Electric Vehicles: A Case Study of Java Island - Wicaksono, Surya Adi; Huboyo, Haryono Setiyo; Samadikun, Budi Prasetyo; Joyosemito, Ibnu Susanto (Universitas Diponegoro, 2024)
In order to mitigate the impact of climate change arising from Greenhouse Gas (GHG) emissions generated from the transportation sector, many countries including Indonesia, have initiated to develop policies to encourage environmentally friendly transportation technologies. Electric vehicles represent a highly sustainable alternative when compared to conventional vehicles. This study aims to assess the potential reduction of GHG emissions from the shifting to electric vehicle utilization on Java Island. The research method was conducted by modeling conventional vehicles until 2033 where there was a transition to electric vehicles throughout the model year and then calculating the GHG emission. This study employs three scenarios : Business As Usual (BAU), Electric Vehicle Plan (EVP) with existing scenario power plant and Electric Vehicle Plan (EVP) with National Energy Plan (NEP) scenario power plant. Model results revealed potential GHG emission reductions within 12.11% from the Existing EVP scenario and 12.54% from the NEP scenario against the BAU scenario due to the shifting usege of electric vehicles on Java island. Based on the model results, it is possible to determine that shifting from conventional vehicles to electric vehicles can reduce GHG emissions from conventional vehicle use.